Cultural Models of Substance Misuse Risk and Moral Foundations: Cognitive Resources Underlying Stigma Attribution - Henderson, Nicole Lynn (Journal of cognition and culture, 2019)
This study examines the cognitive resources underlying the attribution of stigma in substance use and misuse. A cultural model of substance misuse risk was elicited from students at a major U.S. state university. We found a contested cultural model, with some respondents adopting a model of medical risk while others adopted a model of moral failure; agreeing that moral failure primarily defined risk led to greater attribution of stigma. Here we incorporate general beliefs about moral decision-making, assessed through Moral Foundations Theory. Specifically, we examined commitment to each moral foundation in relation to stigma attribution while controlling for the specific model of substance misuse risk. We found an interaction between the purity moral foundation and the cultural model of risk. This suggests that broad moral orientations, along with more specific understandings of substance misuse risk, combine to orient an individual with respect to stigma attribution.